Identification of potential natural inhibitors of SARS-CoV2 main protease by molecular docking and simulation studies. Issue 12 (13th August 2021) - Gupta, Sanjay; Singh, Atul Kumar; Kushwaha, Prem Prakash; Prajapati, Kumari Sunita; Shuaib, Mohd; Senapati, Sabyasachi; Kumar, Shashank
Abstract: Coronaviruses are contagious pathogens primarily responsible for respiratory and intestinal infections. Research efforts to develop antiviral agents against coronavirus demonstrated the main protease (Mpro) protein may represent effective drug target. X-ray crystallographic structure of the SARS-CoV2 Mpro protein demonstrated the significance of Glu166, Cys141, and His41 residues involved in protein dimerization and its catalytic function. We performed in silico screening of compounds from Curcuma longa L. (Zingiberaceae family) against Mpro protein inhibition. Employing a combination of molecular docking, scoring functions, and molecular dynamics simulations, 267 compounds were screened by docking on Mpro crystallographic structure. Docking score and interaction profile analysis exhibited strong binding on the Mpro catalytic domain with compounds C1 (1E, 6E)-1, 2, 6, 7-tetrahydroxy-1, 7-bis(4-hydroxy-3-methoxyphenyl)hepta-1, 6-diene-3, 5-dione) and C2 (4Z, 6E)‐1, 5‐dihydroxy‐1, 7‐bis(4‐hydroxyphenyl)hepta‐4, 6‐dien‐3‐one as lead agents. Compound C1 and C2 showed minimum binding score (–9.08 and –8.07 kcal/mole) against Mpro protein in comparison to shikonin and lopinavir (≈ −5.4 kcal/mole) a standard Mpro inhibitor. Furthermore, principal component analysis, free energy landscape and protein-ligand energy calculation studies revealed that these two compounds strongly bind to the catalytic core of the Mpro protein with higher efficacy than lopinavir, a standard antiretroviral of the protease inhibitor class. Taken together, this structure based optimization has provided lead on two natural Mpro inhibitors for further testing and development as therapeutics against human coronavirus. Communicated by Ramaswamy H. Sarma